Analisa Sistem Akuntansi Aktiva Tetap pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Solok Selatan - Roza Junita; Zulsantoni Zulsantoni; Dakhyar Dakhyar; Fatma Yeni (Strata Business Review, 2023)
This research was conducted at PDAM Solok Selatan Regency. PDAM Solok Selatan Regency is an agency engaged in services in service and organizing benefits in the field of drinking water which will be distributed to the people of South Solok. The data in this study came from primary data, namely data obtained by observation, documentation and interviews. After the data is collected, it will be analyzed using a qualitative descriptive analysis method, meaning data analysis by describing the status or phenomenon that contains information to provide an overview of the fixed asset accounting system at PDAM Solok Selatan Regency. The results of the research conducted at the Solok Selatan District PDAM are that the way to acquire fixed assets at the PDAM is by purchasing them ready-to-use, built in advance and receiving gifts. The documents used are requisitions for goods, purchase orders, receipts, work orders, proof of requisitions for goods and issuance of goods. PDAM Solok Selatan Regency applies the straight-line method of depreciation. The application of fixed asset accounting at PDAM Solok Selatan Regency has not been implemented properly. Because the PDAM of Solok Selatan Regency is only guided by SAK ETAP, it's just that not all of which in the classification of fixed assets in PDAM of Solok Selatan Regency are calculated over 5 years are included in fixed assets while in PSAK rules No 16 in the classification calculated over 1 year are stated as fixed assets.